Final Answer:
The expression (4y^6)^3 - (10z^2)^3 is equivalent to 64y^18 - 1000z^6.
Step-by-step explanation:
Factor out common powers:
64y^18 = (2^6)(y^3)^6
1000z^6 = (10^3)(z^2)^3
Rewrite the expression with factored terms:
64y^18 - 1000z^6 = (2^6)(y^3)^6 - (10^3)(z^2)^3
Apply power of a power rule:
(a^m)^n = a^(mn)
(2^6)(y^3)^6 = 2^(66) * y^(36) = 2^36 * y^18
(10^3)(z^2)^3 = 10^(33) * z^(2*3) = 10^9 * z^6
Substitute back the simplified terms:
2^36 * y^18 - 10^9 * z^6 = (4y^6)^3 - (10z^2)^3
Therefore, (4y^6)^3 - (10z^2)^3 is the equivalent expression to 64y^18 - 1000z^6. Both expressions involve the difference of cubes of binomials, with one focusing on powers of 4y^6 and the other emphasizing powers of 10z^2.